Sistem Informasi Manajemen Aset TI Pada Kementerian Agama Kota Probolinggo - Zulfikar Rahman; Arifin Puji Widodo; Anjik Sukmaaji (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
ABSTRACT: IT assets in Kota Probolinggo Religious Affairs is an operational support to any existing activities, so that the existing IT assets must be maintained condition and functionality. In the procurement planning process takes two months because he did not know the value of the economic life and in the process of planning the removal may also experience problems because the office does not use basic planning deletion based on the value of depreciation of assets, maintenance-related information and a list of damaged IT assets.Based on the existing problems, then solved by making IT asset management information system. In this system there is the process of inventory of IT assets, calculation of depreciation by the straight-line method, IT asset procurement planning, maintenance of IT assets and planning the elimination of IT assets.Information systems IT asset management is able to generate reports estimate the maintenance of IT assets, reports the economic life of less than one year, reports the economic life of the asset is close to 0, the report IT assets that pass through the economic life, the report IT assets active, reports loaning IT assets, reports depreciation, reports procurement planning new IT assets, IT asset maintenance schedule reports, report maintenance costs, reports IT assets that have been wiped out, and reports removal plan. With a percentage of 98% successful testing so that applications be valid for use.Keywords: System Information, Asset Management, IT Asset